O44-1 Pestipop: a french generic job-exposure matrix for use in epidemiological studies on occupational exposure to pesticides. (1st September 2016) - Carles, Camille; Bouvier, Ghislaine; Lebailly, Pierre; Baldi, Isabelle
Abstract : Occupational exposure to pesticides concerns a wide population of workers, not only in agriculture but in numerous other occupational industries, including gardeners/landscapers, pest killers, workers in wood industry. The reliability of self-reported information on lifelong use of pesticides is questionable because of the large range of molecules possibly used. So are biological measurements because of the short half-life of most pesticides. The PESTIPOP job-exposure matrix, which is under development, intends to estimate parameters of pesticide occupational exposure in the French general population. The current version of the matrix is composed of two axis: the first axis corresponding to occupations (combinations of jobs and industries classified according to the French classifications of the National Institute for Statistics and Economic Studies) and the second one to pesticide exposure (globally and in four categories: insecticides, herbicides, fungicides, others). The estimated exposure metric is the probability of exposure coupled with a reliability level (low, medium or high). These metrics were defined by combining different sources: i) an a priori expert assessment (panel of agricultural industry experts); ii) data collected in a multicentric case control study (596 cases and 1192 controls) on brain tumours in the general population (occupational history, specific questionnaires); iii) an a posteriori expert assessment by consensus among three experts, based on the data of the case control study. So far, 105 occupations (24 in agriculture) and 77 industries (14 in agriculture) were classified as exposed to pesticides, corresponding to 166 occupation-industry pairs. For example, youth workers in training centres had a probability of 33% to be exposed to insecticides and herbicides whereas teachers in nursery or primary schools had a probability of 25% to be exposed to insecticides according to the matrix. Transcoding into international classifications (ISOC, ISIC) will follow to allow comparison with international existing matrices.